2021
DOI: 10.1155/2021/4743971
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Immune-Related Signatures and Immune Infiltration Analysis in Melanoma

Abstract: In the present study, we aimed to investigate immune-related signatures and immune infiltration in melanoma. The transcriptome profiling and clinical data of melanoma were downloaded from The Cancer Genome Atlas database, and their matched normal samples were obtained from the Genotype-Tissue Expression database. After merging the genome expression data using Perl, the limma package was used for data normalization. We screened the differentially expressed genes (DEGs) and obtained immune signatures associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The diagnosis, evaluation, and treatment of cancer are closely related to the tumor immune microenvironment, especially to the infiltrating immune cells [14][15][16]. Recent research has confirmed that lncRNAs are critical regulators of gene expression in the immune system; lncRNAs direct the expression of genes related to the development/activation of diverse immune cells, impacting tumor immune cell infiltration and, consequently, the immune microenvironment [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis, evaluation, and treatment of cancer are closely related to the tumor immune microenvironment, especially to the infiltrating immune cells [14][15][16]. Recent research has confirmed that lncRNAs are critical regulators of gene expression in the immune system; lncRNAs direct the expression of genes related to the development/activation of diverse immune cells, impacting tumor immune cell infiltration and, consequently, the immune microenvironment [17,18].…”
Section: Introductionmentioning
confidence: 99%